Feasibility and usefulness of a consumer-grade device for physical activity monitoring for patients with Parkinson's disease and Parkinsonism - Tropea, P.; Judica, E.; Seregni, A.; Caprino, M.; Corbo, M. (Gait & posture, 2022)
The identification of the best measures to improve quality of life, awareness and care management for senior users with neurodegenerative diseases, and the implementation of personalized recommendations to support the user through gamification techniques and to adopt healthy habits, to maintain a good daily routine and to follow the prescribed actions by professionals for maintaining and improving their health condition, are the main contributions of PROCare4Life, an EU funded project. In fact, by proposing an integrated scalable and interactive care ecosystem, this solution can be easily adapted to the reality of several chronic diseases. The ability to passively track continuous ambulatory activity over time in a real-world scenario in patients with Parkinson’s disease (PD) has many potential uses. Wrist-worn physical activity monitors may be a valuable tool for tracking and/or increasing physical activity among patients with Parkinson. Because of differences in technology acceptance associated with age, and variable clinical conditions, feasibility and usefulness of Fitbits may vary among these subjects. The purpose of this study was to evaluate the patients’ adherence during the period of physical activity monitoring and to analyze the correlation between steps counts and clinical parameters. Patients with idiopathic PD (Parkinson’s disease) or Parkinsonism were recruited at Casa di Cura del Policlinico (Milan, Italy). Participants attended one assessment session at hospital with an expert neurologist. Age, gender, disease duration, falls history and medication intake were collected by an interview. Disease severity was measured using the Unified Parkinson’s Disease Rating Scale (UPDRS) and stage of disease rated using Hoehn and Yahr scale (H&Y). All participants signed an informed consent. All research procedures were approved by the Local Ethics Committee. Patients’ physical activity monitoring was performed by means of the wearable sensor Fitbit Versa 2 (Fitbit Inc, San Francisco, California, USA), a small wearable activity tracker that is worn like a watch with a triaxial accelerometer and that displays step count. The activity tracker was provided to patients at the time of enrollment together with the instructions for use. Patients were asked to wear it at all times for 60 days, excluding while bathing and sleeping. Step count was recorded while participants wore the smartwatch. While no specific recommendations were given on amount of physical activity and there was no daily step target, patients were invited to follow their daily routine for the period of the monitoring. Correlation between step count data from the Fitbit, demographic indicators and clinical scales were examined using Pearson’s correlation coefficient. 13 subjects were enrolled (73.23 ± 6.56 years; 8 males; 10 with diagnosis of PD; UDPRS at baseline: 67.92 ± 35.30; H&Y: 2.69 ± 0.75). Three of the 13 participants did not complete the study due to wristband’s usability problems. Among the subjects that completed the study, the number of mean daily steps during the monitoring period was 4879.76 ± 3385.69, with individual participants’ means ranging from 62.54 to 11727.86. The majority of subjects (60%) could be classified as sedentary (i.e., mean daily steps lower than 5000) [1]. Using the adherence definition of >100 steps, on average the participants wore wristband 49.80 ± 16.86 days, with an adherence of 83.00 ± 28.11% of the 60-day study period. Noteworthy, for the quasi-totality of subjects (70%) the adherence was very high (96.67 ± 5.69%), for two participants was high (68.33-75.00%) and for one participant very low (10.00%). A significant correlation between steps taken and UPDRS (R= -0.76, p=0.010) at the end of the monitoring period was found. Removing the subjects with very low adherence and the one that never reached 5000 steps per day, a high significant correlation for steps taken and H&Y scale (R = 0.71, p = 0.047) resulted. An additional high significant correlation was found between steps taken and the differences in global score of UPDRS (R = 0.75, p = 0.031) assessed at the beginning and at the end of the monitoring period. The preliminary results show that the use of a consumer-grade device in patients with neurodegenerative disease is feasible with reasonable adherence. The positive correlation between steps taken and modification in UPDRS scales means that higher steps correspond to a smaller worsening in UPDRS scale assessment. These preliminary results, if confirmed in large scale scenario, could be useful in the framework of the PROCare4Life project, in order to develop and validate an ICT-based integrated care ecosystem that will improve the quality of life of the users in their care delivery, and by improving social and medical services through automation and digitalisation.